Shiga toxin-producing Escherichia coli outbreaks in California’s leafy greens production continuum - Lacombe, Alison; Quintela, Irwin A.; Liao, Yen-Te; Wu, Vivian C.H. (Frontiers in Food Science and Technology, 2022)
Despite efforts to control pathogenic hazards in agriculture, leafy greens grown in California were the source of several high-profile outbreaks of Shiga toxin-producing E. coli (STEC). The U.S. Food and Drug Administration (FDA) analysis of the outbreaks found three reoccurring patterns with leafy greens contaminated with STEC, specifically E. coli O 157:H7, in 2018–2020: the presence of pathogenic E. coli, common geographical regions, and issues with activities on adjacent lands, such as cattle production and migratory birds. The FDA’s response to the recurring outbreaks associated with leafy greens is the Leafy Greens STEC Action Plan (LGAP). In partnership with the U.S. Environmental Protection Agency (EPA), a regulatory pathway was created for the approval of commercial sanitizers that can be applied to agricultural irrigation water to combat STEC, specifically E. coli O 157:H7. However, the protocol has several real-world limitations and economic consequences, such as the potential to overuse sanitizing products, thus adding disinfection by-products classified as pollutants. In addition, there have been several initiatives due to systems research on the local, state, and federal levels to provide technical assistance for the further improvement of Good Agricultural Practices (GAPs). This review considers the factors involved in leafy green production, such as agricultural water, climate change, and adjacent land use, contributing to increased susceptibility to pathogens contamination and how the implementation of sanitizers impacts food safety. The review discusses potential future improvements to agricultural water safety and quality in the context of improving food safety.